Inpatient Consultation Communication: Hospital Culture and Perspectives [15I]. Issue 1 (May 2017) - Heiselman, Cassandra; Smelcer, Philip; Shah, Khooshali; Cottrell, Connie; Lavin, Justin
Abstract : INTRODUCTION: Obstetrical and Gynecological consultations are a significant component of the workflow within the healthcare system. Ineffective consult-related communication can lead to poor outcomes, costly medical errors, and suboptimal medical care. METHODS: This was a cross sectional mixed quantitative/qualitative survey design evaluating physicians' perception regarding the inpatient consultation process. Physicians were asked to rank inpatient services with regards to quality of communication when requesting a consultation, to indicate the importance of specific behaviors during the consultation process, to assess the need for change, and to make suggestions for improvement. RESULTS: 243 (32.4%) of 750 physicians completed the questionnaire. The OBGYN services ranked second for quality of communication as both the consultant and the consulter with only the Medical Subspecialties service ranking higher (p < 0.0001). Across specialties, the most important consultation elements identified were asking a clear question (91.2%) and answering the initial page in a timely fashion (84.3%). The distribution of consultation components considered essential differed across specialty groups (p < 0.0001). Direct communication by the consultant (p < 0.0001) and the consulter (p < 0.0001) were considered critical elements by OBGYN physicians. 89.5% of all physicians perceived a need for change within the consultation culture. The most frequent suggestion for improvement was direct physician-to-physician communication. CONCLUSION: Different specialties consider different consultation components essential, making it challenging for OBGYN physicians to effectively communicate with other services. Results suggest the need for well-designed hospital guidelines for consultations that include direct communication between providers and clear, specific clinical questions.